Development of a Performance Model for SMEs to Go International in Aceh Barat Regency to Strengthen the Coastal Economy - Shifa, Mutiara; Hidayat, Muhammad Rahmat; Rusdi, Rusdi; Husen, Tamitha Intassar (Pusat P2M Politeknik Negeri Batam, 2025)
This study examines the relationships between export orientation, social capital, strategic competitiveness, and export performance within the context of firms operating in international markets. Utilizing a theoretical framework based on the Resource-Based View (RBV) and Cadogan's epistemology, the research explores the role of social capital as an intangible resource that can enhance export performance and the contribution of export orientation as a driver of strategic competitiveness. The analysis results reveal a significant impact of export orientation on strategic competitiveness (P-Value 0.000), yet it does not demonstrate a direct significant effect on export performance (P-Value 0.139). Conversely, social capital has a highly significant impact on export performance (P-Value 0.000) and export orientation (P-Value 0.000), but it does not significantly influence strategic competitiveness (P-Value 0.249). Furthermore, strategic competitiveness significantly affects export performance (P-Value 0.000). These findings suggest that while both export orientation and social capital play vital roles in enhancing export performance, firms must develop robust strategic competitiveness to achieve success in the global market. This research provides insights into the importance of integrating social resources, export orientation, and competitive strategies to achieve optimal export performance.